How breastfeeding behavior develops in women with gestational diabetes mellitus: A qualitative study based on health belief model in China - Qian, Pan; Duan, Lixia; Lin, Rujiao; Du, Xiwang; Wang, Dan; Liu, Chenxi; Zeng, Tieying (Frontiers in Endocrinology, 2022)
Background Gestational diabetes mellitus (GDM) is a condition in which women develop hyperglycemia during pregnancy, and is associated with long-term health burden on both mother and their offspring, such as future type 2 diabetes mellitus (T2DM). Although breastfeeding was expected to mitigate metabolic sequelae for both mothers and their newborns, the prevalence of breastfeeding in GDM mothers are sub-optimal worldwide. Objective To explore the experience of disease among mothers with GDM and how they develop feeding behaviors. Methods This study was conducted in three branches of an integrated tertiary hospital in the central area of China. Mothers who were diagnosed with GDM, had no other complications, and gave birth before no more than 6 months were approached based on a purposive sampling. GDM mothers’ experience of the disease and breastfeeding were collected via in-depth interviews. A theory-driven thematic analysis based on Health Belief Model (HBM) was applied for data analysis. Inductive reasoning was used to identify emerging themes which were not included in HBM. Results 16 GDM mothers were included in the current study, with nine using breastfeeding, six mixed feeding and one artificial feeding, respectively. Nine themes were identified, including: 1) GDM diagnosis and severity; 2) information searching and GDM knowledge;3) GDM management; 4) perceived susceptibility of future diabetes;5) perceived severity of future diabetes;6) perceived benefits of breastfeeding;7) perceived barriers of breastfeeding;8) decision making process of feeding and social support. Generally, mothers with GDM lack reliable sources of information, considered the disease as a minor and transient illness during pregnancy, and failed to realize the long-term risk of GDM and the protective effect of breastfeeding to themselves and their babies. They rarely considered GDM in their feeding decision. Instead, the formation of feeding behaviors depends on the balance between the benefits and barriers of breastfeeding as well as the level of social support. Conclusion To promote breastfeeding, a multi-facet intervention targeted on healthcare providers (HCPs), GDM mothers and their networks was important to help GDM mothers better and correctly understand the disease and breastfeeding, and increase their capacity of breastfeeding.